229k views
3 votes
Helppppppppppppppppppppppppppppppppppppp

Helppppppppppppppppppppppppppppppppppppp-example-1
User Sandeep R
by
5.4k points

1 Answer

7 votes
The second choice, y+1=6/11(x+4), is correct.

We first find the slope using the formula

m=(y₂-y₁)/(x₂-x₁)

Using our points, this gives us
m=(-1-5)/(-4-7) = -6/-11 = 6/11

Point-slope form is
y-y₁=m(x-x₁)

Using the first point, we would have
y-5=6/11(x-7)

Using the second point, we would have
y--1=6/11(x--4)
y+1=6/11(x+4)
User Karl Von L
by
5.3k points